A Holistic Performance Assessment of English Premier League Football Clubs 1992–2013 - Daniel Plumley; Robert Wilson; Simon Shibli (Journal of Applied Sports Management, 2017)
This paper devises and tests a statistical model (the PAM) to measure the financial and sporting performance of professional football clubs. The PAM has been applied to a longitudinal data set of English football clubs (21 clubs between 1992–2013) to identify trends in performance. The results show that a small number of clubs have created an imbalance within English football and that there has been evidence of a “financial crisis” at individual clubs. For the majority of clubs, overall performance appears to vary over time in cycles. In addition to measuring holistic performance of professional football clubs in England, the paper has developed a statistically robust model that progresses research in the field. This new model has the potential to be adapted to fit other professional team sports to test league viability. It can also be used by the clubs themselves to set objectives and to analyse performance against competitors.
Keywords: Economics; sports; finance; football; profit maximisation; utility maximisation